Laminin Levels as a Biomarker for Liver injury in Methamphetamine Addict - Sami, Shahbaa W.; Mahmood, Halla Gh. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Methamphetamine (METH) is a potent synthetic stimulant that significantly impacts the central nervous system and can lead to severe liver damage. Prolonged METH use causes hepatocytes damage and fibrosis, marked by increased laminin deposition, a key component of the extracellular matrix produced by stellate cells during liver injury.Objectives: This study aimed to investigate the effects of METH abuse on liver function and laminin (LN) levels, correlating these with the duration and concentration of METH use.Methods: Conducted from January to August 2024, this case-control study involved 75 male participants with METH addiction (6-120 months of use) and 75 healthy controls aged 18-51. Key biomarkers were measured, including serum laminin, aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), Gamma-Glutamyl Transferase (GGT), albumin and the serum concentration of methamphetamine levels.Result: The study revealed a significant increase in serum laminin, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and Gamma-Glutamyl Transferees. The notable significant decrease in albumin was detected. Additionally, the study demonstrated a positive correlation between LN levels and the duration of drug abuse, as between the concentration of methamphetamine levels with aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, Gamma-Glutamyl Transferees, and albumin, and correlation between methamphetamine of duration with aspartate aminotransferase, alanine aminotransferase, Gamma-Glutamyl Transferees.Conclusions: The results indicate that METH addiction leads to elevated laminin levels and liver enzyme activity, suggesting progressive liver fibrosis and injury correlating with the duration of substance abuse.